Tracheal cross-protection against enteric strains of infectious bronchitis virus by a conventional vaccine - BHATTACHARJEE, P S; SAVAGE, C E; JONES, R C (The Indian Journal of Animal Sciences, 2013)
A cross-protection trial against several enteric isolates of IBV was carried out using a commercial M41 type vaccine. All chickens immunized with this vaccine were strongly protected against homologous strain at the tracheal level, both in vitro and in vivo mode systems used in this study. The most surprising result was that vaccine strain and Dutuch47/82(D207) belong. to the same tracheal protectotype. The serum of the vaccinated birds was also assessed by the conventional serum neutralization test (betha method) in TOCs.